Multiculturalism, Culture Mixing, and Prejudice: Effects of Priming Chinese Diversity Models Among Hong Kong University Students - Ye, Frank Tian-Fang; Buchtel, Emma E. (Frontiers in Psychology, 2021)
In two studies, we investigated how Hong Kong university students reacted to descriptions of China as multicultural vs. assimilatory, examining effects on emotions, prejudice towards mainland Chinese, attitudes towards Hong Kong / China culture mixing, and cultural identities. Study 1 compared a multicultural priming condition to a control condition and found that the multiculturalism prime significantly reduced desire to socially distance from Mainland Chinese. Study 2 compared multiculturalism, assimilation, or control primes’ effects, and found that the multiculturalism prime, through increased positive emotions, indirectly reduced social distancing from mainland Chinese and disgust towards culture mixing, and increased Chinese ethnic identity and multicultural identity styles; the assimilation prime had the opposite indirect effects through increasing negative emotions. Results show new evidence of the importance of emotion in how non-immigrant regional groups, who are both minority and majority culture members, react to different diversity models. Multicultural frames increased positive emotions, with downstream positive effects on both intergroup attitudes and integrated identities.